2004
DOI: 10.1093/ajcn/80.4.887
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid supplementation, insulin sensitivity, and lipoprotein metabolism in patients with type 2 diabetes mellitus

Abstract: CLA supplementation had an adverse effect on insulin and glucose metabolism. Whereas CLA had positive effects on HDL metabolism and fibrinogen, a therapeutic nutrient should not be associated with potentially adverse effects on other clinical markers of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
179
5
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(205 citation statements)
references
References 49 publications
15
179
5
6
Order By: Relevance
“…One study using an oral glucose tolerance test (OGTT) reported in improved insulin sensitivity in healthy subjects after intake of the CLA mixture. 16 On the other hand, in a study of type 2 diabetics, 17 16 subjects receiving a mixture of CLA isomers showed changes in fasting glucose, HOMA, insulin sensitivity index and oral glucose sensitivity suggestive of increased insulin resistance compared to placebo-treated subjects. In the same study, however, no changes in HbA1c, QUICKI, fasting insulin or glucose and insulin response during OGTT, were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study using an oral glucose tolerance test (OGTT) reported in improved insulin sensitivity in healthy subjects after intake of the CLA mixture. 16 On the other hand, in a study of type 2 diabetics, 17 16 subjects receiving a mixture of CLA isomers showed changes in fasting glucose, HOMA, insulin sensitivity index and oral glucose sensitivity suggestive of increased insulin resistance compared to placebo-treated subjects. In the same study, however, no changes in HbA1c, QUICKI, fasting insulin or glucose and insulin response during OGTT, were observed.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] CLA as a food supplement is widely promoted for reduction of body fat. Long-term studies have shown CLA to be safe.…”
Section: Introductionmentioning
confidence: 99%
“…The c9,t11 isomer of CLA is the major form of naturally occurring CLA, and is found in dairy products and ruminant meats. Additionally, a mixture of the c9,t11-and t10,c12-CLA isomers is available in health food stores as a dietary supplement, and is being evaluated clinically for its potential benefit in controlling obesity, improving immune function and insulin sensitivity, and altering lipid metabolism [1][2][3]. CLA has also been shown to be an anticancer agent in a number of rodent and human tumor model systems, including carcinogen-induced and transplantable mammary tumor models [4].…”
Section: Introductionmentioning
confidence: 99%
“…Com exceção do trabalho de Belury et al 94 , que observaram redução da glicose plasmática em indivíduos portadores de diabetes tipo 2, a maioria dos estudos revisados demonstrou aumento de glicose plasmática, tendência para aumento da insulina plasmática e redução da sensibilidade à insulina 8,65,79,90,95 . Apenas os trabalhos recentes de Tricón et al 80 e de Taylor et al 96 reúnem dados que os permitem concluir que ambos os isômeros de CLA não apresentaram efeitos adversos sobre as concentrações plasmáticas de glicose e insulina e sobre a sensibilidade à ação da insulina.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified
“…A partir de então muitos foram os estudos com diversos animais [102][103][104] , com culturas de adipócito de roedores e humanos [105][106][107][108][109] e com humanos 8,65,[74][75][76][77][78][79][80]90,95,96,[110][111][112][113][114][115][116] , que surgiram com o objetivo de avaliar a propriedade de redução da gordura corporal, bem como elucidar os mecanismos de ação pelos quais o CLA desempenha esse papel.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified